(untitled) (Dhaka University Journal of Biological Sciences, 2021)
The study was conducted to prepare a database for the infection status of protozoan parasites on an important host fish species of Bangladesh, Heretropneustes fossilis. Host samples were collected from the freshwater habitats of six different districts of Bangladesh- Manikganj, Faridpur, Mymensingh, Kishoreganj, Bogura, and Jashore. H. fossilis was noted to be infected by 6 parasite species, of which 3 belonged to myxozoa (Henneguya singhi, Henneguya qadrii and Henneguya mystusia); 1 belonged to ciliophora (Trichodina siddiquae) and 2 (Trypanosoma singhii and Piscinoodium pillulare) belonged to mastigophora.The parasites, Trypanosoma singhii and Henneguya singhi were recorded as new locality record in H. fossilis. The three parasites Piscinoodium pillulare, Henneguya qadrii and Henneguya mystusia were the first recorded parasites in this fish and the first locality record in Bangladesh. The parasites were observed to occupy gill, body slime, and blood. Gill parasites were abundantly found compared to body slime and blood parasites. The highest prevalence (67.21%) of infection of H. fossilis was observed in Manikganj and the lowest prevalence (54.67%) of infection was observed in Bogura. Parasites of H. fossilis showed the highest diversity in fishes of Faridpur (2.63). Species richness of parasites was highest in Manikganj (0.38) and species evenness was relatively low (0.13-0.19) in almost all the study sites. Dhaka Univ. J. Biol. Sci. 30(2): 307-316, 2021 (July)